On fixed points of set-valued directional contractions - Sehie Park (International Journal of Mathematics and Mathematical Sciences)
Using equivalent formulations of Ekeland's theorem, we improve fixed point theorems of Clarke, Sehgal, Sehgal-Smithson, and Kirk-Ray on directional contractions by giving geometric estimations of fixed points.